Comparision of Parent Reported Sleeping Habits and Sleep Problems Between Attention Deficit and Hyperactivity Disorder and Healthy Controls - Yusuf Ozturk; Gonca Ozyurt; Aynur Pekcanlar Akay (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Attention Deficit and Hyperactivity Disorder (ADHD) children has been shown to affect the quality of sleep. In this study it is aimed to evaluate sleep habits and sleep problems between the cases who are diagnosed with ADHD and healthy controls. The study group consisted of 61 children (8-12 years old) with ADHD; the control group (87 children) comprised patients of other clinics at hospital. The Kiddie Schedule for Affective Disorders and Schizophrenia for School Aged Children-Present and Lifetime Version (K-SADS-PL) and DuPaul ADHD Rating Scale vere used. Children's sleep habits and sleep problems were assessed with the Children's Sleep Habits Questionnaire. ADHD group compared to healthy controls; statistical significant difference was found in bedtime resistance, the sleep onset delay, the sleep duration, the sleep anxiety, the night wakings, the parasomnias and the daytime sleepiness but statistical significant difference wasnt found the sleep disordered breathing. In our study, problems in the sleep habits evaluated by parents ADHD are more than campared with healty controls likewise literature. However, further studies with larger sample size and objective measures such as actigraphy and polysomnography may allow us to have more knowledge in this area. [JCBPR 2017; 6(3.000): 108-114]